Monitoring costs, credit constraints and entrepreneurship - Banerji, Sanjay; Raj, Rajesh S.N.; Sen, Kunal (Wiley, 2016)
Access to finance is seen as a binding constraint on the growth of household enterprises in developing countries. We develop a principal-agent model of a household enterprise and show that limited access to finance and monitoring costs constrain the firm size via both a direct and indirect effect. While greater access to finance has a positive direct effect on the hiring of paid labour, firms may not choose to expand and use paid labour, via an indirect route which operates through the monitoring costs of employing paid workers. We use large nationally representative surveys of household enterprises in Indian manufacturing and find support for the predictions of our theory.